Sky boys : how they built the Empire State Building - Hopkinson, Deborah; Ransome, James (New York : Dragonfly., 2006)
In 1931, a boy and his father watch as the world's tallest building, the Empire State Building, is constructed, step-by-step, near their Manhattan home.
M
b
b
Keywords: Empire State Building (New York, N.Y.) -- Design and construction -- Fiction; Skyscrapers -- Fiction; Building -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction